Applied General-Equilibrium Models of Taxation and International Trade: An Introduction and Survey - Shoven, John B.; Whalley, John (Journal of Economic Literature, 2008)
We wish to acknowledge the help of three referees and of John Pencavel on several earlier drafts, as well as the assistance of the modelers, whose work is referred to in the paper. They corrected our lack of understanding of their work and provided many other helpful comments. Excellent research and bibliographical assistance have been provided by Debbie Fretz, Radwan Shaban, and Janet Stotsky. Helpful comments have been made by Charles Ballard, Michael Boskin, Lans Bovenberg, Sylvester Damus, Harvey Galper, Glenn Harrison, Gordon Lenjosek, Jack Mutti, Serena Ng, T. N. Srinivasan, Charles Stuart, and Eric Toder. The authors also acknowledgefinancial support from the National Bureau of Economic Research, the National Science Foundation, International Business Machines, and the Social Sciences and Humanities Research Council: Ottawa, Canada.